Japanese and Indonesian Relative Clausa Patterns - Ngurah Indra Pradhana (KIRYOKU, 2021)
In this research, the object of study is clause. This research is focused on the derivation of clauses known as relative clauses. In this study, it was examined about the differences and similarities in the formation patterns, meanings, and relation characteristics of clauses which are relatively good in two languages, namely between Japanese and Indonesian. The results of this research can be used in the teaching and learning process. As well as useful for readers and audiences who intend to pursue linguistics. The analytical method used in this research is the agih method. Based on the analysis that has been done, several conclusions can be drawn as follows. In Indonesian, a relative clause is indicated by the word "yang" as a conjunctive pronoun. Relative clauses can be used as an expansion technique. There is a slight difference in the formation of Relative Clauses in Indonesian and Japanese, namely, in Indonesian the relative clause can only consist of the word "yang" as a relative clause marker and a predicate which functions as a modifier which is then followed by a core sentence. Whereas in Japanese, a relative clause consists of a minimum of objects and a predicate as a modifier followed by a core sentence. Semantically, relative clauses are viewed from proportions formed by a predicate which states activities, processes, or circumstances. The characteristic of the relation in a relative clause is indicated by the word that comes after the noun.